2012
DOI: 10.1111/j.1476-5381.2011.01705.x
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism and pharmacokinetics of phospho‐sulindac (OXT‐328) and the effect of difluoromethylornithine

Abstract: BACKGROUND AND PURPOSEPhospho-sulindac (PS; OXT-328) prevents colon cancer in mice, especially when combined with difluoromethylornithine (DFMO). Here, we explored its metabolism and pharmacokinetics. EXPERIMENTAL APPROACHPS metabolism was studied in cultured cells, liver microsomes and cytosol, intestinal microsomes and in mice. Pharmacokinetics and biodistribution of PS were studied in mice. KEY RESULTSPS undergoes reduction and oxidation yielding PS sulphide and PS sulphone; is hydrolysed releasing sulindac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 44 publications
(67 reference statements)
1
30
0
Order By: Relevance
“…This family of enzymes play a critical role in the inactivation of xenobiotics (14, 15). Carboxylesterases hydrolyze phospho-NSAIDs at the carboxylic ester bond, leading to the release of the native NSAID and the phospho-moiety (16, 17). Cell lines engineered to overexpress CES 1 or CES 2 actively hydrolyse phospho-NSAIDs, leading to strong resistance to their cytotoxic effects (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This family of enzymes play a critical role in the inactivation of xenobiotics (14, 15). Carboxylesterases hydrolyze phospho-NSAIDs at the carboxylic ester bond, leading to the release of the native NSAID and the phospho-moiety (16, 17). Cell lines engineered to overexpress CES 1 or CES 2 actively hydrolyse phospho-NSAIDs, leading to strong resistance to their cytotoxic effects (16).…”
Section: Introductionmentioning
confidence: 99%
“…Cell lines engineered to overexpress CES 1 or CES 2 actively hydrolyse phospho-NSAIDs, leading to strong resistance to their cytotoxic effects (16). In rodents, carboxylesterase-mediated inactivation of phospho-NSAIDs occurs very rapidly, resulting in very low concentrations of the intact drug in the plasma and organs (17, 18). Importantly, there are considerable differences in the expression of carboxylesterases between humans and rodents.…”
Section: Introductionmentioning
confidence: 99%
“…The remarkable safety of PS (far superior to that of sulindac) is largely explained by its unique pharmacokinetic properties: its blood area under the curve concentration from 0 to 24 hours is around 40% of that of sulindac, and in the stomach, the organ most affected by NSAID toxicity, PS is present mainly intact with minimal levels of its harmful metabolites, sulindac and sulindac sulfide (Xie et al, 2012a). PS's more rapid detoxification by cytochrome P450s and flavin monooxygenases seems to contribute to its safety .…”
Section: Evolving Role Of Nsaids In Colon Cancer Preventionmentioning
confidence: 99%
“…PS exhibited more potent anti-cancer efficacy and markedly reduced toxicity than conventional sulindac in animal models [5]. However, the carboxylester bond of PS is labile, resulting in the extensive hydrolysis of PS to sulindac in vitro and in vivo [6]. We previously demonstrated that protecting PS against its hydrolysis enhanced its anti-cancer efficacy [7].…”
Section: Introductionmentioning
confidence: 99%